Early Identifications of Authorship of the Johannine Writings - Gunther, J. J. (The journal of ecclesiastical history, 1980)
T. W. Manson posed the following problem:…quotations are absent in those places where we should most confidently look lor them it the Fourth Gospel was composed in Ephesus about A.D, 100 by John the Apostle. No theory about the Gospel that fails to give an explanation of the phenomenon presented by the writings of Ignatius, Polycarp and Justin has much chance of survival.No information about the Fourth Gospel or its author appears in the Pastoral Epistles.